EVALUASI KUALITAS LAYANAN SISTEM INFORMASI SHOPEE MENGGUNAKAN METODE WEBQUAL 4.0 (STUDY KASUS CV. PRIMERO LASER INDONESIA) - Dinda Nerissa Arviana; Mohammad Badrul; Wida Prima Mustika; Andi Sanjaya (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2025)
Electronic Commerce (E-Commerce) is a combination of technology business between business people and customers who conduct electronic transactions online. Currently, many people shop online or it can be called e-commerce in Indonesia, such as Shopee. The quality of e-commerce sites can affect the number of customers to make transactions, knowing that the height and quality of the website is determined by Webqual 4.0. The instruments used are validity test and reliability test, partial hypothesis test (T test), simultaneous test (F test) and coefficient of determination test ( . This study aims to obtain value from users and to determine the factors that affect the quality of the Shopee website. To support research, researchers conduct interviews and questionnaires as a method of collecting information. The population in this research are customers/clients who have used the Shopee web as a medium for purchasing goods at CV. Primero Laser Indonesia. 50 respondents have been collected as an illustration in this case it takes 2 (two) weeks of collection. The results of this study have a good and significant effect on the Information Quality variable ( on user satisfaction at CV. Primero Laser Indonesia customers (Y), but there is no good/positive and significant effect between the Usability Quality variable ( and Service Interaction Quality ( to customer satisfaction CV. Primero Laser Indonesia (Y).